Mark Twain and metaphor - Bird, John, 1954-; ebrary, Inc. (Columbia : University of Missouri Press, 2007)
"Examines how Twain used metaphor to express his attitudes and thoughts, revealing not only hidden facets of Twain's artistry but also new aspects of works that we think we know well such as The Adventures of Tom Sawyer, Adventures of Huckleberry Finn, and A Connecticut Yankee in King Arthur's Court"--Provided by publisher.
Figuring "Mark Twain" -- Figuring the river -- Figuring metaphor -- Figuring the end.
Includes bibliographical references (p. 232-241) and index.
Electronic reproduction.
Keywords: Twain, Mark, -- 1835-1910 -- Criticism and interpretation; Twain, Mark, -- 1835-1910 -- Literary style; Metaphor in literature; Electronic books